Elementary School Students' Perceptions of Learning Vocabularies Using Short Stories - Ledy, Neris Mayang; Sujarwati, Iis; Syafryadin, Syafryadin (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Short stories are considered an excellent and highly significant teaching approach in elementary level teaching and learning as they provide a useful and unique learning resource and encourage language acquisition, progress and personal interest. This study aims to better understand how primary school pupils see vocabulary development. A mixed-methods study was conducted with thirty sixth graders at SD IT Cahaya Rabbani Kepahiang to gather both quantitative and qualitative data. To collect quantitative data, a questionnaire was employed, and to collect qualitative data, interviews were used. Using SPSS and Excel, the data were descriptively examined. Because short stories are engaging, practical, and simple to grasp, 80% of SD IT Cahaya Rabbani Kepahiang students highly agree and believe that using short story media can help students learn more words in English. The study's conclusions indicate that students are open to using short stories to broaden their vocabulary and find them engaging. Therefore, English teachers should employ short stories to assist students learn vocabulary. The instructor should be mindful of the significance of selecting short stories wisely and doing it in a way that is both engaging and amusing. The selected short stories must also pay attention to the interests, needs, and skills of students. In this study, only a subset of children from the same school participated. Information was only collected once, through questionnaires and interviews. As a result, only students in the same school can use the findings. Additional research should include more people from various institutions to provide more thorough results. Additionally, it is possible to investigate the effectiveness of using short stories to help students expand their vocabulary by using different research methodologies like experimental or action research.Keywords: Students’ perception; short story; vocabulary